Comparison of the rate of successful endotracheal intubation between the "sniffing" and "ramped" positions in patients with an expected difficult intubation: a prospective randomized study - Lee, Ju-Hwan (Korean J Anesthesiol, 2015)
BACKGROUND: Optimal head and neck positioning and clinical experience are important factors for successful endotracheal intubation in patients with a difficult airway. This study aimed to investigate the rate of successful endotracheal intubation between the sniffing and ramped positions in patients with an expected difficult intubation. METHODS: The study included 204 patients with an expected difficult intubation (airway difficulty score ≥ 8) based on the preoperative airway assessment. The patients were randomized into the following groups: group S was placed in the sniffing position, and group R was placed in the ramped position during direct laryngoscopy. The primary outcome was successful endotracheal intubation and the secondary measure was laryngeal view in the ramped or sniffing position when the operating table was placed at two different heights. RESULTS: Group R showed a higher rate of successful endotracheal intubation and better laryngeal view than group S (P < 0.05). The rate of successful endotracheal intubation was higher in group R than in group S at both heights of the operating table; but, it was not different within each group. Laryngeal view was not different between the two groups and within each group when the two heights of the operating table were used. Fully trained and experienced attending anesthesiologists achieved a higher rate of successful endotracheal intubation than less experienced residents in group R (P < 0.05) but not in group S. CONCLUSIONS: Ramped position and clinical experience can be important factors for laryngeal view and success rate of endotracheal intubation in patients with an expected difficult intubation.